Influence of fly control on incidence of pinkeye and on calf performance - Schalles, R.R.; McKee, M.; Evans, Jack; Davis, Duane L.; Pitts, C.W. Jr. (Kansas State University. Agricultural Experiment Station, 2011)
Controlling flies significantly decreased incidence of pinkeye in cattle on native Flint Hill range. There was no difference in the average weaning weight of groups sprayed or not sprayed. However individuals severely affected with pinkeye were much lighter than the average.
Keywords: Beef; Fly control; Pinkeye; Calf performance